Literature Review: Faktor Risiko Penyebaran Bakteri Penghasil Extended Spectrum Beta Lactamase (ESBL) Pada Neonatus - Terza Aflika Happy; Miratul Hasanah; Agustina Mar’atus Sholichah (NERSMID : Jurnal Keperawatan dan Kebidanan, 2020)
In neonates, infection by ESBL-producing bacteria increases the risk of death, and decelerates time for recovery. Thus, neonates with ESBL infection who require antibiotic therapy will be hospitalized longer than patients who are not infected with ESBL. This causes the cost of hospitalization in the hospital increases. To identify the risk factors of ESBL transmission to neonates. Literature search from journal from January till August 2020 using an online journal database by the keywords ESBL, ESBL neonatus, dan risk factor ESBL. A total of 35 articles are selected because they match the inclusion criteria, namely titles and content relevant to the purpose, written in English or Indonesian, full text, published in the last 7 years. From 14 articles selected for review, information is obtained regarding risk factors for the ESBL transmission to neonates. The risk factors associated with the ESBL transmission to neonates are ages, delivery process, visits to health facilities, and administration of antibiotics.